Effectiveness of Giving Carrot Juice (Daucus Carota l) in Overcoming Nipple Crack and Clogged Milk Duct in Breastfeeding Mother - Senditya Indah Mayasari; Waifti Amalia Waifti; Nicky Danur Jayanti (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2025)
Exclusive breastfeeding remains difficult to achieve, with prevalence still falling short of national and global targets. One contributing factor is the discomfort experienced during nursing, such as nipple cracks and blocked milk ducts, which can reduce milk output and discourage continued breastfeeding. Carrot juice, rich in beta-carotene, vitamin A, and antioxidants, offers anti-inflammatory benefits that may accelerate healing, relieve pain, and prevent complications like mastitis. Given these properties, carrot juice is a simple, natural addition to postpartum care. Carrot juice should be given urgently to breastfeeding mothers as it contains beta-carotene and antioxidants that help reduce inflammation, relieve nipple pain, and prevent blocked milk ducts. This study aimed to determine the effectiveness of carrot juice (Daucus carota L.) in improving breastfeeding outcomes by reducing the incidence of nipple cracks and blocked milk ducts. A quasi-experimental design was used involving 15 breastfeeding mothers. Participants consumed 250 cc of freshly prepared carrot juice daily for seven days. Data were collected before and after the intervention using observation sheets and analyzed with the Wilcoxon test. The results showed a Z value of -3.41 (p=0.001) for nipple cracks and -3.29 (p=0.001) for blocked ducts. Both p-values (< 0.05) indicate significant improvement post-intervention. These findings confirm that regular consumption of carrot juice can effectively reduce the severity of nipple injuries and milk duct blockages. Carrot juice is a low-cost, accessible, and safe nutritional therapy that supports lactation. Further research is recommended to explore its mechanism of action and potential dosage optimization for broader clinical application.